2013
DOI: 10.1152/japplphysiol.00293.2013
|View full text |Cite
|
Sign up to set email alerts
|

Changes in neurochemicals within the ventrolateral medullary respiratory column in awake goats after carotid body denervation

Abstract: A current and major unanswered question is why the highly sensitive central CO2/H(+) chemoreceptors do not prevent hypoventilation-induced hypercapnia following carotid body denervation (CBD). Because perturbations involving the carotid bodies affect central neuromodulator and/or neurotransmitter levels within the respiratory network, we tested the hypothesis that after CBD there is an increase in inhibitory and/or a decrease in excitatory neurochemicals within the ventrolateral medullary column (VMC) in awake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 50 publications
1
31
2
Order By: Relevance
“…2 ). As in our past studies (21, 22), we utilized the breathing frequency response to glutamate agonist (NMDA) injections as a physiologic indicator of MT proximity to the preBötC region. Consistent with past studies, we found variation in this response to NMDA injections (inset in Fig.2 ).…”
Section: Resultsmentioning
confidence: 99%
“…2 ). As in our past studies (21, 22), we utilized the breathing frequency response to glutamate agonist (NMDA) injections as a physiologic indicator of MT proximity to the preBötC region. Consistent with past studies, we found variation in this response to NMDA injections (inset in Fig.2 ).…”
Section: Resultsmentioning
confidence: 99%
“…In animals, the hypoxic ventilatory response recovers partially or totally (rats) over time presumably because of an increase in the activity of the aortic bodies. Postsurgically, carotid body denervation also produces resting hypoventilation and hypercapnia, an effect that decreases days to week after surgery but may never recover completely depending on the species (45, 285, 298). Similar hypoventilation has been observed in man [(443) and references therein].…”
Section: Interplay Between Peripheral and Central Chemoreceptorsmentioning
confidence: 99%
“…Given the apparent absence of plasticity of CO 2 -responsive central chemoreceptors (rats, this study), a slight change in CB sensory transduction could also in theory explain why CBD produces such a long-lasting hypoventilation and rise in PCO 2 set point in large species and not in rats (Forster, 2003;Miller et al, 2013;Angelova et al, 2015). A major species difference in the central circuitry underlying the chemoreflexes need not be invoked to explain these observations.…”
Section: Central Chemoreflex Plasticity After Carotid Body Denervatiomentioning
confidence: 82%
“…This discrepancy implies that some form of central plasticity of the respiratory network unrelated to oxygen sensing develops. This interpretation is supported by evidence of neurochemical changes in the brainstem and of changes in the respiratory stimulation elicited by activating raphe neurons (Hodges et al, 2005;Mouradian et al, 2012;Miller et al, 2013).…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation